Sensualitas Iklan "The Axe Effect" - Didit Widiatmoko Soewardikoen (Wimba : Jurnal Komunikasi Visual, 2010)
Pleasure of viewing used as strategic approach on advertisement. The most attractive and frequent using pleasure of viewing is sensuality. Axe as a product of menâs body odor utilize it as advertisement strategy. These ads become unique because representing a different occurrence that woman pursuing a man. By mean of visual analysis with psychoanalysis approach would be describe how Axe ads persuade the target audience through gestures and sensualities.